EFFECT OF BEHAVIOUR CHANGE COMMUNICATION ON BREASTFEEDING PRACTICES IN PERIURBAN AREA OF ALIGARH - Khan, Mohd. Haroon; Khalique, Najam; Siddiqui, A R; Amir, Ali; Ahmad, Anees; Shah, M Salman; Khan, Ruby (Indian Journal of Community Health, 2012)
Objectives: 1.To assess the behavior of pregnant women regarding breastfeeding practices. 2. Assessing impact of Behavior Change Communication Package among pregnant women regarding breastfeeding practices. Study design: A community based intervention study Setting: Field practice areas of Urban Health Training Center, Department of Community Medicine, JNMCH, AMU, Aligarh. Participants: 200 pregnant women (100 pregnant women from each intervention and non-intervention group) Sampling: Purposive sampling method. Statistical Analysis: Data analysed with Epi Info version 3.5.1. Percentages, Relative Risk and Chi Square Test used. Results: Due to implementation of BCC Package in intervention, good practices like giving colostrum were increased two times. Initiation of breastfeeding within 1 hour was increased 4.7 times, exclusive breastfeeding was gone up 3.8 times for first seven days of delivery. There was significant difference (P–value <0.05) between the two groups regarding breastfeeding on 7th day of delivery. The differences were significant (P–value-<0.05) on 7th and 28th days of delivery. Conclusion: Good practices of breastfeeding within one hour, using colostrum, exclusive breastfeeding were improved significantly after implementation of behavior change communication package.